2015
DOI: 10.1105/tpc.15.00248
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping of Fertility Reduction upon Heat Stress Reveals Developmental Stage-Specific QTLs in Arabidopsis thaliana

Abstract: ORCID ID: 0000-0001-8918-0711 (J.J.B.K.)For crops that are grown for their fruits or seeds, elevated temperatures that occur during flowering and seed or fruit set have a stronger effect on yield than high temperatures during the vegetative stage. Even short-term exposure to heat can have a large impact on yield. In this study, we used Arabidopsis thaliana to study the effect of short-term heat exposure on flower and seed development. The impact of a single hot day (35°C) was determined in more than 250 natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 93 publications
6
77
0
Order By: Relevance
“…1C). High temperature causes infertility in Arabidopsis (Bac-Molenaar et al, 2015), and we found that 30°C is approaching the higher temperature threshold for Col-0. This may explain the reduction in seed set, which also is known to lead to an increase in seed size (Hughes et al, 2008).…”
Section: Temperature Influences the Oil Content Of Arabidopsis Seedsmentioning
confidence: 63%
“…1C). High temperature causes infertility in Arabidopsis (Bac-Molenaar et al, 2015), and we found that 30°C is approaching the higher temperature threshold for Col-0. This may explain the reduction in seed set, which also is known to lead to an increase in seed size (Hughes et al, 2008).…”
Section: Temperature Influences the Oil Content Of Arabidopsis Seedsmentioning
confidence: 63%
“…To identify novel players involved in the effect of SA and ABA on JA‐responsive gene expression, we performed GWA mapping using the ~214k SNP set that is commonly used for GWA studies in Arabidopsis (Atwell et al, ; Bac‐Molenaar et al, ; Horton et al, ; Kim et al, ; Li, et al, ). To this end, we used normally distributed log 2 PDF1.2 gene expression data of the MeJA + SA treatment and the MeJA+ABA treatment, relative to PDF1.2 expression data of the single MeJA treatment [log 2 ( PDF1.2 MeJA+SA /PDF1.2 MeJA )] and [log 2 ( PDF1.2 MeJA+ABA /PDF1.2 MeJA )], respectively (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…However, nonfunctional FRI alleles are associated with negative pleiotropic effects on branching and fitness, likely limiting the adaptive potential of the FRI locus (Scarcelli et al, 2007). Natural variation in FLC and FRI also affects other important life history traits, including seed germination (Chiang et al, 2009), water use efficiency, which is a major dehydration avoidance mechanism (McKay et al, 2003), and even flower tolerance to heat shocks (Bac-Molenaar et al, 2015). FLC also plays a role in more long-lived plants.…”
mentioning
confidence: 99%